"Evaluación del crecimiento y producción de biomasa de dos cepas del genero Pleurotus spp. cultivadas en un medio AGAR con diferentes sustratos" - Coello Loor, Carol Daniela (2012)
The rate of radial growth and the biomass production are techniques that help us understand the degree of adaptation and development of mushrooms of the Pleurotus spp. genus in various substrates which could be applied in a solid medium fermentation. The city of Quevedo has excess residual materials from the agro-industrial practice; such as the rind of passion fruit and rice; which due to their volume made it attractive to conduct this investigation. The medium for the synthetic culture that was utilized for these tests was potato dextrose agar (PDA), since it has all the nutritious components for the mushrooms growth; the potato extract provides starch, some lignin and other minerals, the dextrose (glucose) is the primary source of carbon for the mushrooms, and the agar is the added as a gelling agent, its pH (5.6 – 5.9) is ideal for mushroom growth and the inhibition of bacteria growth due to its slight acidity, diluted in 4 different solutions prepared with the residual materials, with the purpose to observe the radial growth every 24 hours and the fungal biomass production of these lignocellulosic mushrooms during their period of incubation and adaptation which they could have in vitro. The species were Pleurotus sapidus and Pleurotus ostreatus IE8. The best VCR (mm h-1) was the strain of the Pleurotus ostreatus (0.569) and the best culture medium for the growth and development of the strains was the CAPDA; whereas the treatments that showed the best results of adaptation in the biomass production (g g-1of dry substrate) were the Pleurotus sapidus with the CAPDA (0.1727), el Pleurotus ostreatus con CMPDA (0.1722), CAPDA (0.1706) and PDA (0.1694). Yellow corn was the grain that demonstrated best results in obtaining the seed from the two strains and the mixture of the two residual substrates at 50% of the fermentation in solid medium; it provided minor difficulties in handling, abundant mycelial growth and compaction of the samples, furthermore, there was presence of primords in the incubated bags after the first 25 days for both strains of the Pleurotus genus.